English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

it says "given that dy/dx = (3-√x)²/√x ,x>0, and that y=2/3 at x=1, find y in terms of x" i really don't understand!

2006-11-27 09:33:31 · 7 answers · asked by Andy P 1 in Science & Mathematics Mathematics

7 answers

dy/dx=(3-√x)²/√x
=(9+x-6*(x)^(1/2)/x^(1/2)
=(9x^(-1/2)+x^(1/2)-6)
dy=(9x^(-1/2)+x^(1/2)-6)dx
integrate
y=int{9x^(-1/2)+x^(1/2)-6}dx
= 18x^(1/2)+2/3x^(1.5)-6x+D
use initial conditions
2/3=18+2/3-6+D
>>D= -12

therefore,
y=2/3x^(1.5)-6x+18x^(1/2)-12

i hope that this helps

2006-11-27 17:37:25 · answer #1 · answered by Anonymous · 0 0

I think it would be best to expand your dy/dx.

dy/dx = (9 - 6√x + x) / √x = 9x^(-1/2) - 6 + x^(1/2)

y = 9x^(1/2)/(1/2) - 6x + x^(3/2)/(3/2) + C
y = 18x^(1/2) - 6x + (2/3)x^(3/2) + C

Substitute x=1 and y=2/3,
2/3 = 18 - 6 + (2/3) + C
C = -18 + 6
C = -12

So,
y = 18x^(1/2) - 6x + (2/3)x^(3/2) - 12
y = 18√x - 6x + (2/3)(√x)^3 - 12

2006-11-27 09:40:42 · answer #2 · answered by Kemmy 6 · 0 0

what it is asking is that you rearrange the formula so that y is the subject and then work out its value. Remember, if you transfer something to the other side of the equals sign you change its sign to the opposite. Alternativly you could put in the values and work it out from there.
I gopt that :
y=9+x -6√x
and then you have to work out the bit about the other stuff, after that i get abit confused too and can't help you.

2006-11-27 09:46:17 · answer #3 · answered by Anonymous · 0 1

No, neither do I.

2006-11-27 09:39:33 · answer #4 · answered by mistickle17 5 · 0 2

???? that is just crazy

2006-11-27 11:12:32 · answer #5 · answered by Anonymous · 0 1

hmmm...

2006-11-27 09:43:13 · answer #6 · answered by QPRfan 6 · 0 1

i don't know!!!

2006-11-27 09:41:39 · answer #7 · answered by Anonymous · 0 2

fedest.com, questions and answers